1992
DOI: 10.1101/gad.6.8.1466
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Id protein inhibits the muscle differentiation program: in vivo association of Id with E2A proteins.

Abstract: The helix-loop-helix (HLH) protein Id lacks the basic DNA-binding domain common to this class of proteins. In vitro experiments suggested that Id could associate tightly with two other HLH proteins encoded by the E2A gene, El2 and E47 (referred to here collectively as E proteins) and prevent their binding to a sequence present in the muscle creatine kinase (MCK) enhancer either as homo-oligomers or hetero-oligomers with MyoD. In this report we present evidence for the in vivo roles of Id and E proteins: (1) Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
365
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(383 citation statements)
references
References 41 publications
14
365
4
Order By: Relevance
“…Quantitative or qualitative changes in Mmip1 might provide a means by which Mad family members could be regulated at the posttranslational level. In this way, Mmip1 may well be functionally analagous to Id proteins which modulate the activity of Class A and B bHLH proteins through the formation of functionally inactive heterodimers (Jen et al, 1992;. The absence of a basic domain in Mmip1 also raises the interesting possibility that it may serve as an Id-like inhibitor of select bZIP proteins, quite apart from the role de®ned here.…”
Section: Endogenous Mmip1 Expression and Co-immunoprecipitation With mentioning
confidence: 83%
“…Quantitative or qualitative changes in Mmip1 might provide a means by which Mad family members could be regulated at the posttranslational level. In this way, Mmip1 may well be functionally analagous to Id proteins which modulate the activity of Class A and B bHLH proteins through the formation of functionally inactive heterodimers (Jen et al, 1992;. The absence of a basic domain in Mmip1 also raises the interesting possibility that it may serve as an Id-like inhibitor of select bZIP proteins, quite apart from the role de®ned here.…”
Section: Endogenous Mmip1 Expression and Co-immunoprecipitation With mentioning
confidence: 83%
“…Also, overexpression of Id2 potentiates proliferation which is likely related to its ability to bind Rb protein [34]. It has been suggested that Id-like transcriptional regulators function as general inhibitors of differentiation and activators of proliferation [23,35]. How these two different functions are coordinated in different cell types remains to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…ID proteins form DNA-binding incompetent heterodimers with bHLH transcription factors thereby inhibiting their transcriptional activities (Benezra et al, 1990). Individual ID-proteins have been linked to inhibiting cellular differentiation, inhibition of bHLHand other transcription factors (Benezra et al, 1990;Jen et al, 1992;Kreider et al, 1992;Ohtani et al, 2001;Roberts et al, 2001), modulating apoptosis (Florio et al, 1998;Ling et al, 2003), cooperating with the retinoblastoma tumor suppressor pathway (Iavarone et al, 1994;Hara et al, 1996), extending cellular life span (Alani et al, 1999;Nickoloff et al, 2000;Tang et al, 2002), regulating angiogenesis (Lyden et al, 2001) as well as cardiac development (Fraidenraich et al, 2004), and stem cell maintenance (Ying et al, 2003). ID expression is induced as part of the immediate-early transcriptional response to growth factors and is regulated in a cell cycle-dependent manner.…”
Section: Introductionmentioning
confidence: 99%